PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2012 s.d 2014 - Siti Fatimah Z; Makhdalena '; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study aims to determine the influence of independent directors and audit committee on the disclosure of corporate social responsibility. This research was conducted in the mining company listed on the Indonesia Stock Exchange 2012 period s.d 2014 with 20 sample obtained using purposive sampling method. The analysis techniques used in this research is multiple linear regression analysis. The result showed that the Independent Commissioner and Audit Committee simultaneously affect the disclosure of corporate social responsibility at 0.383. Furthermore, the results of research partially showing an Independent Commissioner effect on the disclosure of corporate social responsibility at 0.145924. The Audit Committee affect the disclosure of corporate social responsibility at 0.157609.Keywords : Independent Commissioners, the Audit Committee, and the Corporate Social Responsibility Disclosure